Tumors of the Central Nervous System, Volume 12 Molecular Mechanisms, Children's Cancer, Treatments, and Radiosurgery - Hayat, M.A.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2014)
As in the case of its eleven predecessors in the series Tumors of the Central Nervous System, this volume is distinguished for its thorough approach, its roster of 92 distinguished contributors representing 11 different countries and its detailed examination of leading-edge technology and methods. Volume 12: Molecular Mechanisms, Children$1 (Bs Cancer, Treatments, and Radiosurgery offers a comprehensive review of the diagnosis, therapy and prognosis of brain and spinal cord tumors. Coverage extends to a large number of tumor types, including neuroblastoma, medulloblastoma, meningioma and chordoma. Molecular profiling of brain tumors to select appropriate therapy in clinical trials of brain tumors is discussed in detail, as is the classification/diagnosis of brain tumors based on function analysis. CDK6 as the molecular regulator of neuronal differentiation in the adult brain, and the role of aquaporins in human brain tumor growth are explained. Discussion also includes tumors affecting children, including neuroblastoma and medulloblastoma. A full chapter is devoted to the role of molecular genetic alterations in medulloblastoma, and another examines survival differences between children and adults with medulloblastoma. The use of various types of imaging methods to diagnose brain tumors is explained. In-depth discussion of treatment options includes stereotactic radiosurgery, endoscopic neurosurgery, electrochemotherapy, transsphenoidal surgery, focal ablation, whole brain radiation therapy and recraniotomy.s
Preface. I Molecular mechanisms -- Classification/diagnosis of brain tumors using discriminate function analysis -- Neuronal differentiation in the adult brain: cdk6 as the molecular regulator -- Prolactinomas: role of vegf, fgf-2 and cd31 -- Human brain tumor growth: role of aquaporins -- Molecular and functional characterization of human adipocytes -- II Children$1 (Bs cancer -- Inhibition of neuroblastoma progression by targeting Lymphangiogenesis: role of an endogenous soluble splice-variant of vegfr-2 -- Hyperinsulinemia tends to induce growth without growth hormone in children with brain tumors after neurosurgery -- Childhood brain tumors: proton beam therapy -- Pathogenesis of medulloblastoma: role of molecular genetic alterations -- Medulloblastomas: survival differences between children and adults -- Survivors of childhood cancer: risk of glioma and meningioma following radiotherapy -- Survivors of childhood cancer: risk of new primary neoplasms of the cns.-III Treatments -- Brain tumor typing and therapy using combined ex vivo magnetic resonance spectroscopy and molecular genomics -- Atlas-based segmentation of tumor-bearing brain images -- Nonthermal irreversible electroporation as a focal ablation treatment for brain cancer -- The role of whole brain radiation therapy for metastatic brain tumors -- Craniotomy for intracranial tumors: role of postoperative hematoma in surgical mortality -- Pituitary adenomas: treatment using the endonasal approach intracranial tumors: treatment with endoscopic neurosurgery -- Incidence of recraniotomy for postoperative infections after surgery for intracranial tumors -- Transsphenoidal surgery for non-adenomatous tumors: effect on pituitary function -- Treatment of brain tumors: electrochemotherapy -- Comparison of navigated transcranial magnetic stimulation to direct electrical stimulation for mapping the motor cortex prior to brain tumor resection -- The role of glutathione and the glutathione-linked enzyme systems in brain tumor drug resistance -- Drugs for primary brain tumors: an update -- Neurosurgical treatment for brain metastases: clinical features, operative strategies, recurrence, and survival. IV Radiosurgery -- Image-guided radiosurgery for hypothalamic hamartomas -- Image-guided stereotactic radiosurgery for spinal pathology -- Image guided stereotactic radiosurgery for optic nerve sheath meningiomas -- Brain metastases: the application of stereotactic radiosurgery and technological advances -- Treatment of chordomas by stereotactic radiosurgery with a linear accelerator: comparison with other modes. Index.s
Keywords: Medicine; Oncology; Biomedicine; Cancer Research; Oncology; Biomedicine general; Medicine/Public Health, general